2013
DOI: 10.1136/oemed-2013-101490
|View full text |Cite
|
Sign up to set email alerts
|

Biomonitoring of organophosphate exposure of pesticide sprayers and comparison of exposure levels with other population groups in Thessaly (Greece)

Abstract: Our study findings confirm the increased exposure to OPs in pesticide sprayers and underline the importance of protective measures especially those that focus on dermal exposure mitigation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
37
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(43 citation statements)
references
References 33 publications
5
37
1
Order By: Relevance
“…Because DNA damage and oxidative stress have been proposed as possible mechanisms that could explain some health effects related to pesticide exposure, the results in this study are relevant because they suggest an important role of antioxidant enzymes for the protection of DNA damage caused by high occupational exposure to pesticides.…”
Section: Discussionmentioning
confidence: 99%
“…Because DNA damage and oxidative stress have been proposed as possible mechanisms that could explain some health effects related to pesticide exposure, the results in this study are relevant because they suggest an important role of antioxidant enzymes for the protection of DNA damage caused by high occupational exposure to pesticides.…”
Section: Discussionmentioning
confidence: 99%
“…30,31,49 For example, among Japanese food distribution workers included in Ueyama et al’s 31 study, DAP detections ranged from 87% to 100%; the geometric mean for DMP 7.0 µg/g creatinine in the summer and 3.8 µg/g creatinine in the winter, with DEP levels being 0.8 µg/g creatinine in the summer and 1.5 µg/g creatinine in the winter. In a study of Israel adults from the general population conducted in 2011, Berman et al 49 found that DMP was detected for 99% of participants, DMTP for 100%, DMDTP for 73%, DEP for 98%, DETP for 76%, and DEDTP was 44%; these detection levels are somewhat higher than those found for the NC non-farmworkers in this analysis.…”
Section: Discussionmentioning
confidence: 99%
“…2125 However, several recent analyses with farmworkers in Washington, Florida, and North Carolina document continuing substantial exposure to OP pesticides. 2628 Research on OP exposure using the six dialkylphosphate (DAP) urinary metabolites of OP pesticides has been conducted in several non-US agricultural populations, including Mexico, 29 France, 12 Greece, 30 Japan, 31 and Thailand. 32,33 Results from these analyses show a great range in metabolite levels.…”
Section: Introductionmentioning
confidence: 99%
“…Among the professional sprayers there is a widespread praxis of poor pesticide handling such as improper storage, mixing several pesticides, bare hands loading, unhygienic spraying, lack of protective equipment use as well as haphazard disposal [26] of remnants and empty containers. The excess use of pesticides coupled with inadequate personal protection, is likely to increase the exposure dose among sprayers in the area [27]. Despite the contribution of these pesticides in improving agricultural production and protection of the harvests, they threaten the human health as a result of poor protection and indiscriminate use and handling [28].…”
Section: Introductionmentioning
confidence: 99%